Extraction and antiviral activity assessment of compounds from Chondracanthus chamissoi and Chlorella peruviana against serotype 2 dengue virus - Mayta-Huatuco, Egma (2020)
Objective: to extract and determine the antiviral activity of compounds from Chondracanthus chamissoi and Chlorella peruviana against DENV-2 in Vero-76 cells. Materials and methods: carrageenan from Chondracanthus chamissoi and soluble carbohydrates from Chlorella peruviana were extracted, and toxicity tests in VERO-76 cells and antiviral activity were determined. Results: carrageenan from Chondracanthus chamissoi sporophyte and gametophyte phases were obtained, the compound was identified as k-carrageenan using infrared light. Nine sugars (ribose, xylose, arabinose, fructose, mannose, galactose, sucrose, maltose, and lactose) were identified using chromatography in the soluble carbohydrate mix from Chondracanthus chamissoi, and four sugars (glucose, sucrose, maltose, and lactose) from Chlorella peruviana were identified. Compounds from Chondracanthus chamissoi and Chlorella peruviana soluble carbohydrate solutions did not show any cytotoxic effect, carbohydrates from the raw extract from Chlorella peruviana did have this effect. All fractions from the raw extract from the gametophyte phase from Chondracanthus chamissoi were positive in the plate reduction test at 1:5 dilution. K-carrageenan from Chondracanthus chamissoi in both phases, as well as the crude extracts of soluble carbohydrates from Chondracanthus chamissoi and Chlorella peruviana as well as the soluble carbohydrate solution from Chlorella peruviana inhibited growth of dengue virus, but that was not the case with the carbohydrates of the raw extract from Chlorella peruviana. Conclusions: compounds obtained from Chondracanthus chamissoi and Chlorella peruviana show antiviral activity against DENV-2, so it is necessary to continue studies aiming to determine the antiviral potential of these fractioned and purified compounds.